Misvaluation Dynamics in M&A: The Hidden Role of Self-Interested Management - Andreou, Christoforos; Lambertides, Neophytos; Luo, Yun; Ye, Jiaxiang (My University, 2025)
This study investigates the dynamics of misvaluation in mergers and acquisitions (M&As), emphasizing managerial self-interest. Using 2,709 U.S. public deals from 1992 to 2022, we show that the positive relationship between acquirer overvaluation and stock-financed deals is primarily driven by self-interested managers, while non-managerial misvaluation factors have no incremental effect. Strong corporate governance reduces managerial discretion and mitigates the influence of mispricing on payment methods. Consistent with agency theory, acquisitions by overvalued acquirers are associated with poor long-run performance and a higher likelihood of stock price crashes. Our findings underscore the central role of managerial discretion in shaping M&A outcomes.
Keywords: Mergers and acquisitions; Misvaluation; Payment methods; Post-acquisition performance; Stock price crash risk